2018
DOI: 10.1111/jch.13186
|View full text |Cite
|
Sign up to set email alerts
|

Right heart remodeling induced by arterial hypertension: Could strain assessment be helpful?

Abstract: Left ventricular structural and functional changes in patients with arterial hypertension are well established. However, the influence of arterial hypertension on right ventricular (RV) remodeling is still being investigated. The introduction of strain analysis provided an insight into RV function and mechanics. Previous research has demonstrated the predictive value of RV longitudinal strain in patients with various cardiovascular conditions, such as pulmonary hypertension, heart failure, congenital heart dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 40 publications
0
20
1
Order By: Relevance
“…We used joint modeling of multiple diseases to capture the effect of hypertension to investigate geographic variations in risk. 69 Recent studies reported that congestive heart failure, 70,71 atrial fibrillation, 72 and peripheral artery disease 73 are highly related to hypertension and could be used as proxies for hypertension. Although we do not have any variable directly reflecting hypertension, we could assume that we have controlled the effect of hypertension because we have included the above-mentioned 3 diseases as proxies for hypertension and added them to the final model (Supplemental Result 2, available online at http://www.mayoclinicproceedings.org).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…We used joint modeling of multiple diseases to capture the effect of hypertension to investigate geographic variations in risk. 69 Recent studies reported that congestive heart failure, 70,71 atrial fibrillation, 72 and peripheral artery disease 73 are highly related to hypertension and could be used as proxies for hypertension. Although we do not have any variable directly reflecting hypertension, we could assume that we have controlled the effect of hypertension because we have included the above-mentioned 3 diseases as proxies for hypertension and added them to the final model (Supplemental Result 2, available online at http://www.mayoclinicproceedings.org).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Our previous studies showed that RV structure, function, and mechanics were impaired in various subtypes of hypertensive patients (white‐coat and masked hypertension, prehypertension, nighttime hypertension, metabolic syndrome) . The influence of gender on RV structure and function in patients with metabolic syndrome and arterial hypertension has already been investigated .…”
Section: Introductionmentioning
confidence: 99%
“…Despite cost-effectiveness and wide availability of echocardiography, RV anatomy and positioning within the chest leads to reproducibility issues with ultrasoundbased strain assessments (Bossone et al, 2013). Additionally, unlike the LV, circumferential and radial ultrasound-based strains are challenging to measure for the RVFW (Tadic et al, 2018). cMRI is a more accurate technique for in vivo RVFW strain measurements.…”
Section: Effects Of Pah On Rv Wall Stress and Contractile Strainsmentioning
confidence: 99%